This site is supported by donations to The OEIS Foundation.

Annual Appeal: Please make a donation (tax deductible in USA) to keep the OEIS running. Over 5000 articles have referenced us, often saying "we discovered this result with the help of the OEIS".

 Hints (Greetings from The On-Line Encyclopedia of Integer Sequences!)
 A177184 Sequence defined by the recurrence formula a(n+1)=sum(a(p)*a(n-p)+k,p=0..n)+l for n>=1, with here a(0)=1, a(1)=9, k=-1 and l=-1. 1
 1, 9, 15, 107, 479, 3103, 18031, 117727, 755599, 5064687, 34093263, 234114735, 1620229839, 11340760367, 79951746767, 567945479727, 4058390653647, 29163273207087, 210568996777167, 1527068200329007, 11117641676731087 (list; graph; refs; listen; history; text; internal format)
 OFFSET 0,2 LINKS FORMULA G.f f: f(z)=(1-sqrt(1-4*z*(a(0)-z*a(0)^2+z*a(1)+(k+l)*z^2/(1-z)+k*z^2/(1-z)^2)))/(2*z) (k=-1, l=-1). Conjecture: +(n+1)*a(n) +(-7*n+2)*a(n-1) +(-17*n+43)*a(n-2) +(95*n-298)*a(n-3) +4*(-28*n+113)*a(n-4) +40*(n-5)*a(n-5)=0. - R. J. Mathar, Mar 02 2016 EXAMPLE a(2)=2*1*9-2-1=15. a(3)=2*1*15-2+81-1-1=107. MAPLE l:=-1: : k := -1 : m:=9:d(0):=1:d(1):=m: for n from 1 to 30 do d(n+1):=sum(d(p)*d(n-p)+k, p=0..n)+l:od : taylor((1-sqrt(1-4*z*(d(0)-z*d(0)^2+z*m+(k+l)*z^2/(1-z)+k*z^2/(1-z)^2)))/(2*z), z=0, 30); seq(d(n), n=0..30); CROSSREFS Cf. A177183. Sequence in context: A029712 A136353 A136354 * A098146 A124274 A075134 Adjacent sequences:  A177181 A177182 A177183 * A177185 A177186 A177187 KEYWORD easy,nonn AUTHOR Richard Choulet, May 04 2010 STATUS approved

Lookup | Welcome | Wiki | Register | Music | Plot 2 | Demos | Index | Browse | More | WebCam
Contribute new seq. or comment | Format | Style Sheet | Transforms | Superseeker | Recent | More pages
The OEIS Community | Maintained by The OEIS Foundation Inc.